Vaiyākaraṇānāmanyeṣāṃ ca matena śabdasvarūpatacchaktivicāraḥ - Śukla, Kālikāprasāda, 1921- (Sarasvatībhavana-adhyayanamālā ; 25., 1979)
Treatise on semantic considerations in Sanskrit grammar, poetics, and some schools of Indic philosophy.